Penerapan Pendekatan Matematika Realistik terhadap Kemampuan Pemahaman Konsep Matematis Siswa - Ridhaningtyas, Latifa Putri; Putra, Eka Cahya Sari (ARZUSIN, 2025)
Mathematics is often perceived as a difficult subject by students, particularly at the elementary and secondary levels, which affects their conceptual understanding. This study aims to examine the effect of the Realistic Mathematics Approach (Pendekatan Matematika Realistik/PMR) on improving students’ conceptual understanding of mathematics through a systematic review and meta-analysis of relevant literature. A quantitative method was employed using a systematic review and meta-analysis approach on 12 scholarly articles published between 2016 and 2020, sourced from the ERIC, Sage, and Google Scholar databases. The analyzed articles focused on the implementation of PMR across various educational levels. The findings indicate that PMR significantly enhances students’ conceptual understanding of mathematics, particularly when compared to conventional instructional approaches. Furthermore, PMR has also been shown to improve mathematical problem-solving skills. The conceptual understanding in question includes the ability to restate a concept and to formulate necessary and sufficient conditions in one’s own words, representing lower-order thinking skills at the C2 level. These findings affirm that integrating PMR into the learning process enables students to relate mathematical concepts to real-life contexts, strengthens understanding, and promotes improved academic achievement. Therefore, PMR can be recommended as an effective instructional strategy to enhance students’ conceptual understanding of mathematics.